Strategi Deep Learning pada Pembelajaran IPAS Digital Berbasis Meaningful, Mindful, dan Joyful Learning : Deep Learning Strategies in Digital Science Education Based on Meaningful, Mindful, and Joyful Learning - Prasetiya, Uki Adi; Rohman, Akhmad Dalil; Sari Asih, Tri Unggul; Mahmudah, Umi (Institut Agama Islam Daruttaqwa Gresik, 2025)
The development of digital technology has brought significant changes to the learning of Natural and Social Sciences in elementary schools, requiring learning strategies that not only utilize technology but also foster deep understanding and active student engagement. This paper aims to analyze the application of learning strategies oriented toward meaningful learning, mindful learning, and joyful learning as the foundation for deep learning within digital learning environments. The method used is library research by reviewing publications from 2021 to 2025 obtained from reputable academic databases. The analysis was conducted to identify key themes related to the contribution of meaningful, mindful, and joyful approaches to strengthening the quality of digital learning. The findings show that meaningful learning helps students connect abstract concepts with real-life experiences, mindful learning enhances focus and emotional regulation in digital environments that are full of distractions, while joyful learning plays a role in increasing intrinsic motivation and active student participation. These three approaches collectively support the development of deep learning that integrates cognitive, affective, and metacognitive aspects. The conclusion of this study emphasizes that digital learning design must be developed comprehensively by integrating meaningful, mindful, and joyful strategies to produce deep, adaptive learning processes that meet the demands of 21st-century education.